2010
DOI: 10.1213/ane.0b013e3181e329f1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Perioperative Blood Transfusion and Blood Conservation in Cardiac Surgery Clinical Practice Guidelines of the Society of Thoracic Surgeons and the Society of Cardiovascular Anesthesiologists upon Clinical Practices

Abstract: Wide variation in clinical practices of cardiac surgery was reported. Little change in clinical practices was attributed to the Society of Thoracic Surgeons/Society of Cardiovascular Anesthesiologists Guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…AmSECT was involved in preparation of the blood transfusion management guidelines established by the collaboration of 2 academic societies, 10) and the temperature management guidelines for extracorporeal circulation were prepared in 2015 by the collaboration of 3 academic societies. 11) In addition, the registration items of extracorporeal circulation cases were reflected in the standard extracorporeal circulation techniques published by AmSECT and guidelines, 12) showing that the summation and analysis by the registration of extracorporeal circulation cases are admitted as scientific evidence.…”
Section: ⅲ.Discussionmentioning
confidence: 99%
“…AmSECT was involved in preparation of the blood transfusion management guidelines established by the collaboration of 2 academic societies, 10) and the temperature management guidelines for extracorporeal circulation were prepared in 2015 by the collaboration of 3 academic societies. 11) In addition, the registration items of extracorporeal circulation cases were reflected in the standard extracorporeal circulation techniques published by AmSECT and guidelines, 12) showing that the summation and analysis by the registration of extracorporeal circulation cases are admitted as scientific evidence.…”
Section: ⅲ.Discussionmentioning
confidence: 99%
“…Although guidelines are regularly updated, implementation and compliance remain poor [14]. Prolonged turnaround times for conventional coagulation tests, which are typically quoted at 60-90 min, are one of the major explanations for this variability, as many transfusions are based on clinical judgement, rather than on real-time information.…”
Section: Rationale For Using Poc Monitoringmentioning
confidence: 99%
“…Indeed, previous studies have shown that many physicians are unaware of guideline content in this important area and may lack the scientific basis to make a valid risk-versus-benefit assessment. 1 In our current era of shared decision making and patient-centered care, it is vital that physicians counsel patients with accurate information. It behooves physicians, therefore, to acquire the necessary knowledge to address patient-specific risk during the informed consent process and to make their patients aware of all available alternative therapies.…”
Section: Commentmentioning
confidence: 99%